Offsite building methods – the building practitioners’ perspective in real estate development - Parpah, Senanu Kwawukume Jnr. (2016)
A thesis submitted to the Department of Building Technology, College of Art and Built Environment, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the Degree of Master of Science in Construction Management,